Using TPM to ensure security, trust and privacy (STP) in VANET - Sumra, I.A. (Institute of Electrical and Electronics Engineers Inc., 2015)
Safety and non-safety applications of VANET provides solutions for road accidents in current traffic system. Security is one of the key research area for successful implementation of safety and non-safety applications of VANET in real environment. Trust and Privacy are two major components of security and dynamic topology and high mobility of vehicles make it more challenging task for end users in network. We propose a new and practical card-based scheme to ensure the Security, Trust and Privacy (STP) in vehicular network. Proposed scheme is based on security hardware module i-e trusted platform module (TPM). The basic objective of proposed scheme is to create trusted security environment for end users in network and user take benefits of potential application of VANET. Â© 2015 IEEE.